2021
DOI: 10.1371/journal.pone.0253800
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies adapted by Ghanaians during the COVID-19 crisis and lockdown: A population-based study

Abstract: Background The COVID-19 pandemic and control measures adopted by countries globally can lead to stress and anxiety. Investigating the coping strategies to this unprecedented crisis is essential to guide mental health intervention and public health policy. This study examined how people are coping with the COVID-19 crisis in Ghana and identify factors influencing it. Methods This study was part of a multinational online cross-sectional survey on Personal and Family Coping with COVID-19 in the Global South. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“… Li et al (2021) discovered that students who adopted coping strategies which focused their attention on solving the problem experienced lower levels of psychological distress. Iddi et al (2021) also revealed that individuals who were concerned about their safety amidst COVID-19 coped very well. Other studies have also shown that religious coping was associated with COVID-19 related anxiety ( Chow et al, 2021 ; Yıldırım et al, 2021 ; Zarrouq et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… Li et al (2021) discovered that students who adopted coping strategies which focused their attention on solving the problem experienced lower levels of psychological distress. Iddi et al (2021) also revealed that individuals who were concerned about their safety amidst COVID-19 coped very well. Other studies have also shown that religious coping was associated with COVID-19 related anxiety ( Chow et al, 2021 ; Yıldırım et al, 2021 ; Zarrouq et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…While facing these unprecedented emergencies and institutions striving to enhance the safety of the school environment (i.e., positive school climate), students could rely on their personal resources to cope with events they may perceive as challenging or threatening ( Peters and McEwen, 2015 ; Peters et al, 2017 ; Alsukah et al, 2020 ). Prior research has shown that coping strategies of persons are related to their level of anxiety and stress (see Main et al, 2011 ; Lyons et al, 2016 ; Iddi et al, 2021 ; Li et al, 2021 ). Li et al (2021) discovered that students who adopted coping strategies which focused their attention on solving the problem experienced lower levels of psychological distress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HSBs of the developing nations would allow for the identifying and prioritizing resource-efficient disease management approaches to control the spread of COVID-19 in their countries [ 37 ]. Likewise, it is essential to identify the coping strategy to deal with the challenging circumstances associated with the ongoing COVID-19 pandemic or other health crises [ 38 ]. The utilization of coping strategies and HSB is influenced by different factors such as demographics, gender, pre-existing health conditions, type of employment, education level, ethnic practices, and disease patterns [ 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is also worth noting that individuals interviewed were mainly university staff, employed, and living in an urban setting, which does not necessarily give an accurate representation of the situation, as surveys would not have represented more vulnerable populations such as rural subsistence farmers, women-headed households or individuals that are not highly educated. Iddi et al reported that 12% of Ghanaians surveyed through an online questionnaire about stress levels linked to well-being felt stressed about the possibility of getting COVID-19, thus causing food insecurity [ 21 ]. The study group was mainly composed of young people (56% under 34, 86% under 44, and 44% having no children), 79% lived in urban Ghana, 98.7% possessed a post-secondary education level, and 72% were employed by the government.…”
Section: Resultsmentioning
confidence: 99%